Hydrophobic interaction chromatography of proteins: Studies of unfolding upon adsorption by isothermal titration calorimetry. Issue 15 (26th June 2018) - Rodler, Agnes; Beyer, Beate; Ueberbacher, Rene; Hahn, Rainer; Jungbauer, Alois
Abstract: Heat of adsorption is an excellent measure for adsorption strength and, therefore, very useful to study the influence of salt and temperature in hydrophobic interaction chromatography. The adsorption of bovine serum albumin and β‐lactoglobulin to Toyopearl Butyl‐650 M was studied with isothermal titration calorimetry to follow the unfolding of proteins on hydrophobic surfaces. Isothermal titration calorimetry is established as an experimental method to track conformational changes of proteins on stationary phases. Experiments were carried out at two different salt concentrations and five different temperatures. Protein unfolding, as indicated by large changes of molar enthalpy of adsorption Δ h ads, was observed to be dependent on temperature and salt concentration. Δ h ads were significantly higher for bovine serum albumin and ranged from 578 (288 K) to 811 (308 K) kJ/mol for 1.2 mol/kg ammonium sulfate. Δ h ads for β‐lactoglobulin ranged from 129 kJ/mol (288 K) to 186 kJ/mol (308 K). For both proteins, Δ h ads increased with increasing temperature. The influence of salt concentration on Δ h ads was also more pronounced for bovine serum albumin than for β‐lactoglobulin. The comparison of retention analysis evaluated by the van't Hoff algorithm shows that beyond adsorption other processes occur simultaneously. Further interpretation such as unfolding upon adsorption needs other in situ techniques.